Longitudinal prevalence of atopic dermatitis among freshmen at Hiroshima University between 2002 and 2019. Issue 7 (22nd March 2022) - Kan, Takanobu; Tanaka, Akio; Kanamoto, Mayu; Morioke, Satoshi; Takahagi, Shunsuke; Hide, Michihiro
Abstract: The prevalence of atopic dermatitis (AD) has been steadily increasing in recent decades, reaching a steady plateau at the end of the 20th century. However, most of them were surveys of children, and the current prevalence and severity of AD in adults are unknown. A longitudinal survey including 40 649 freshmen attending Hiroshima University between 2002 and 2019 was conducted, with the aim to determine changes in AD prevalence in young adults over the age of 18 years. All data were longitudinally collected at a fixed time of the year. The AD diagnosis and severity assessment were made by dermatologists based on the diagnostic criteria in the Japanese Guidelines for AD. History or comorbidities of asthma and allergic rhinitis/conjunctivitis, current AD management, and use of topical corticosteroids (TCS) were also surveyed using a questionnaire. The prevalence of AD in university freshmen is slightly increasing from 9.1% in 2002 to 12.0% in 2010, remaining steady at around 10–11% until 2019, with poorly controlled AD present in nearly 10%. History or comorbidities of asthma and allergic rhinitis/conjunctivitis slightly increased from 2006 to 2019 in both the students with and without AD. Facial eczema was common among those with severe and most severe AD, whereas approximately 50% of the students with moderate AD and approximately 20% of those with mild AD exhibited facial eczema. The percentage of students treating AD at medical institutions and those self‐managing was almost the same. This survey also revealed the presence of substantial anxiety regarding TCS use for AD and the necessity of promoting more effective explanation and education on AD by medical professionals.